(untitled) (International relations and international law Journal, 2016)
Article is devoted to the analysis of peaceful atom development at the present stage. The unstable environment of the world markets, low rates after crisis recovery of the economy of industrial and developing countries have serious impact on a situation in world power, doing more and more actual questions of an assessment of prospects of its development in global power space. Growth of nuclear branch specific weight in world power balance became the most considerable phenomenon of the last decades. In article theoretical approaches and policy of atomic energy formation are studied. Evolution of nuclear branch which is divided into four stages is briefly stated. The question of nuclear power advantage before other power sources is considered. Also the nuclear energy potential to the Republic of Kazakhstan is analyzed importance of use and development of peaceful atom in Kazakhstan is defined. Dynamics of nuclear power development shows that it can and become capable in the future one of major factors of social and economic development majority of the states majority.